Central and peripheral neuromuscular fatigue following ramp and rapid maximal voluntary isometric contractions - Dalton, Benjamin; Hester, Garrett; Alesi, Michaela; McDougle, Jacob; Cooper, Michael; VanDusseldorp, Trisha; Buresh, Robert; Feito, Yuri (Frontiers in Physiology, 2024)
Maximal voluntary isometric contractions (MVICs) as a fatiguing modality have been widely studied, but little attention has been given to the influence of the rate of torque development. Given the established differences in motor command and neuromuscular activation between ramp and rapid MIVCs, it is likely performance fatigue differs as well as the underlying physiological mechanisms. Purpose: To compare responses for rapid and maximal torque following ramp and rapid MVICs, and the corresponding neuromuscular and corticospinal alterations. Methods: On separate visits, twelve healthy males (22.8 ± 2.5 yrs) performed fatiguing intermittent MVICs of the knee extensors with either 2 sec (RAMP) or explosive (RAPID) ramp-ups until a 50% reduction in peak torque was achieved. Before and after each condition, maximal and rapid torque measures were determined from an MVIC. Additionally, peripheral (twitch parameters) and central (voluntary activation) fatigue, as well as rapid muscle activation, and cortical-evoked twitch and electromyographic responses were recorded. Results: Maximal and late-phase rapid torque measures (p ≤ 0.001; η_(p )^2= 0.635 – 0.904) were reduced similarly, but early rapid torque capacity (0-50 ms) (p = 0.003; d = 1.11 vs p = 0.054; d = 0.62) and rapid muscle activation (p = 0.008; d = 1.07 vs p = 0.875; d = 0.06) decreased more after RAMP. Changes in peripheral fatigue, as indicated by singlet and doublet contractile parameters (p < 0.001 for all; η_(p )^2= 0.752 – 0.859), and nerve-evoked voluntary activation (p < 0.001; η_(p )^2= 0.660) were similar between conditions. Corticospinal inhibition (via silent period) was only increased after RAPID (p = 0.007; d = 0.94 vs p = 0.753; d = 0.09), whereas corticospinal voluntary activation and excitability were unchanged. Conclusions: Ramp, fatiguing MVICs impaired early rapid torque capacity more than rapid MVICs, and this was accompanied by decrements in rapid muscle activation. Responses for peripheral and central fatigue (nerve and cortical stimulation) were largely similar between conditions, except that rapid MVICs increased corticospinal inhibition.